Analisis Faktor-Faktor yang Mempengaruhi Investasi Swasta di Jawa Tengah Tahun 1999-2020 - Risma Ayu Istiqomah; Muhammad Arif (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2023)
This research is entitled "Analysis of Factors Affecting Private Investment in Central Java in 19992020". The purpose of this study is to determine theeffect of each independent variable, namely the effect of exchange rates, inflation, interest rates, and labor on private investment (PMA and PMDN) in Central Java in 1999- 2020. The data used in this study is time seriesdata from 1999-2020 obtained from various sources including the Central Statistics Agency (BPS), Bank Indonesia, (DPMPTSP) Central Java Province. The analytical tool used in this study is the OLS (Ordinary Least Square) method. The results of this study indicate that the independent variable that has a significant influence on Private Investment is the Exchange Rate(KURS) variable. While the variables of Inflation, Bank Indonesia Interest Rates, and Manpower did not have a significant effect on the Private Investment variable in Central Java in 1999-2020.